PENERAPAN STANDAR RESEP DALAM PEMBUATAN PEMBUATAN PRODUK BAKERY DI PESONNA HOTEL PEKANBARU - Arum Puspita Rina; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In bakery productions, Pesonna Hotel Pekanbaru definitely has stages of implementation, both in terms of ingredients supply, how to make it, packaging, and distribution. It aims to make bakery products that will be consumed by consumers become a product that has good quality and quantity. This study aims to determine the application of standard recipes in the manufacture of bakery product at Pesonna Hotel Pekanbaru. Standard recipe is a reference used by cooks in processing a food product where in the recipe there are several instructions such as ingredients, quantities, equipments, process of cooking, portions, and other instructions that are very important to apply. This standard recipe aims to maintain the consistency of food both in terms of taste, appearance, portions produced, and the standard time required for processing. This study was conducted using qualitative research method by making 2 key informants as speakers, namely one person cook pastry and one person cook helper. Data collection techniques used in this study are observation, interview, and documentation. Data analysis techniques used in this study are data reduction, data presentation, and end with conclusion. Seen based on research that has been done, the application of standard recipe in the manufacture of bakery product at Pesonna Hotel Pekanbaru has been correctly done. It’s just negligence from its own human resources that causes the standard recipe that have been applied to be failed. Keywords: Application, Standard Recipe, Hotel, Bakery